Haematological variations in visually anaemic sheep naturally infected with Haemonchus contortus in farm conditions at arid Rajasthan - SWARNKAR, C P; SINGH, D (The Indian Journal of Animal Sciences, 2018)
With an objective to reduce use of anthelmintic frequency, targeted selective treatment was implemented for farm flocks in arid Rajasthan. An eye color chart developed by CSWRI, Avikanagar was used for screening the flocks at monthly interval from July to March each year (from 2008 to 2016). All the scorings were done on the same day along with collection of faecal and blood samples from visually anaemic sheep and estimated faecal egg counts (FECs) and erythron parameters, respectively. Data generated were used to establish relationship among haematological estimates and intensity of strongyle infection in visually anaemic sheep. Out of 687 visually anaemic sheep, maximum proportion (54.1%) was recorded in monsoon (Jul-Sep). The frequency distribution exhibited a maximum of 36.3% of visually anaemic sheep with high level (>2001 epg) of strongyle infection. The mean intensity of strongyle infection in visually anaemic sheep varied significantly (P<0.001) from nil (nil epg group) to 8631.6±491.3 epg (>2001 epg group). A significant (P<0.001) influence of strongyle infection level was observed on Hb, PCV and mean corpuscular haemoglobin concentration (MCHC). The overall Hb concentration varied (P<0.001) from 5.7 (>2001 epg) to 7.2g% (nil epg). The overall magnitude of PCV exhibited a linear decline with an increased level of infection and varied (P<0.001) from 15.7 (>2001 epg) to 20.5% (nil epg). MCHC showed a marginal but significant (P<0.001) increase in sheep with >2000 epg compared to other groups. The Pearson correlation coefficient exhibited negative correlation between intensity of strongyle infection and haematological parameters like HB, PCV and TEC in all FEC levels, but it was significant (P<0.001/0.05) only in sheep with FEC >2001 epg. Periodic monitoring of intensity of worm infection and status of anaemia in host animals are an important part of parasite management programmes which aim to avoid both serious parasitism and excessive chemical treatments.